2017
DOI: 10.1177/1750635217728092
|View full text |Cite
|
Sign up to set email alerts
|

Journalism under pressure in conflict zones: A study of journalists and editors in seven countries

Abstract: Through interviews with 100 journalists and editors in seven countries, the authors examine safety as the main challenge for journalists covering war and conflict in both local and international contexts. The article places a particular focus on the situation for Filipino and Norwegian journalists. The underreporting of legal aspects of international conflict, combined with less security, means less presence and more journalistic coverage based on second-hand observation. The article argues that reduced access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 2 publications
1
26
0
1
Order By: Relevance
“…Furthermore, Peter du Toit (2015) argued that a journalist must also inform the conflict to the reader with a detailed event and consider various factors in its coverage. In addition, Hoiby and Ottosen (2017) emphasised that a journalist must be able to get access from both conflicting parties. Without access to conflict areas, the news created by journalists cannot be objective.…”
Section: War/violence Orientedmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Peter du Toit (2015) argued that a journalist must also inform the conflict to the reader with a detailed event and consider various factors in its coverage. In addition, Hoiby and Ottosen (2017) emphasised that a journalist must be able to get access from both conflicting parties. Without access to conflict areas, the news created by journalists cannot be objective.…”
Section: War/violence Orientedmentioning
confidence: 99%
“…Without access to conflict areas, the news created by journalists cannot be objective. The difficulty in accessing conflict areas can lead to biased coverage and have an impact on the decline in journalistic quality (Hoiby & Ottosen, 2017).…”
Section: War/violence Orientedmentioning
confidence: 99%
“…We have found three limitations in previous studies of journalist safety. First, we found that most studies on the safety of journalists stemmed out of conflict and reporting of war zones (Ashry, 2019;Aslam, 2015;Creech, 2018;Düsterhöft, 2013;Eide, Khalvatgar, & Shirzad, 2019;Greppi, 2004;Høiby & Ottosen, 2017;Kim, 2010;Lisosky & Henrichsen, 2009;Relly & Bustamante, 2014;Saboory et al, 2017;Tumber, 2006). Journalists' safety in stable authoritarian or hybrid regimes like Bangladesh hardly gets scholarly attention.…”
Section: The Scope Of This Study: Safety Of Journalists In Bangladeshmentioning
confidence: 99%
“…In this context, some major media organizations have lost the trust of their audiences and have been accused of serious ethical violations for not criticizing actions of the government. As some critics have pointed out, the Pentagon's embedded journalism system, which first emerged as a way to manage strategic media during the Iraq War, called into question the integrity of journalism in the US media (LeBlanc, 2013;Høiby & Ottosen, 2019). Kellner (2008, p. 299) also argued that during the Gulf War in 1991, the Afghanistan War in 2001 and the Iraq War in 2003, newspapers, radio and television (454) Onur Dursun, Filiz Yıldız, Serkan Bulut Moment Journal, 2019, 6(2): 447-469 broadcasting enforced the messages of the army and the state whereas critical approaches were rare.…”
Section: Photojournalism and Visualization Of Warmentioning
confidence: 99%